2017
DOI: 10.1016/j.jconrel.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

How do megakaryocytic microparticles target and deliver cargo to alter the fate of hematopoietic stem cells?

Abstract: Megakaryocytic microparticles (MkMPs), the most abundant MPs in circulation, can induce the differentiation of hematopoietic stem and progenitor cells (HSPCs) into functional megakaryocytes. This MkMP capability could be explored for applications in transfusion medicine but also for delivery of nucleic acids and other molecules to HSPCs for targeted molecular therapy. Understanding how MkMPs target, deliver cargo and alter the fate of HSPCs is important for exploring such applications. We show that MkMPs, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
123
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 63 publications
(128 citation statements)
references
References 69 publications
5
123
0
Order By: Relevance
“…We have previously shown that MkMPs were enriched in small RNAs, 16 which play an important role in triggering Mk differentiation of HSPCs. 16,17 We hypothesized that miRs are the dominant MkMP components in inducing and promoting Mk differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that MkMPs were enriched in small RNAs, 16 which play an important role in triggering Mk differentiation of HSPCs. 16,17 We hypothesized that miRs are the dominant MkMP components in inducing and promoting Mk differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that MkMPs were enriched in small RNAs, 16 which play an important role in triggering Mk differentiation of HSPCs. 16,17 We hypothesized that miRs are the dominant MkMP components in inducing and promoting Mk differentiation. To characterize and carry out comparative analysis of the MkMP miR profile, total RNA was extracted from day-12 cultured Mks (starting from CD34 + cells of 3 donors), MkMPs and platelet-like particles (PLPs) generated from the corresponding day-12 cultured Mks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations